State of the art in physical activity and sport sciences from the analysis of the 6th International Conference of the Spanish Sport Sciences Association: management and scientific perspectives - R. Reina (Asociación Española de Ciencias del Deporte, 2010)
This paper analyzes, from a qualitative and quantitative and qualitative point of view, the scientific production presented in 6th International Conference of the Spanish Sports Sciences Association, held in Elche in October 2010. It exposes the main contributions in sports training, exercise physiology, sport biomechanics, physical activity and health, control and motor learning, sports psychology, teaching in physical education and sport, recreation and sports management. We analyze the participation of researches from the Spanish universities in order to establish a global perspective of the main centres of scientific production. Additionally, some recommendations for future are: i) to achieve higher scientific standards (e.g. to accept only abstracts that use the scientific method and to carry out peer review process), ii) better definition of the thematic areas to evaluate abstracts; iii) to identify hot topics in the thematic areas to establish the estate of the art; iv) more abstracts presented from a biological perspective, v) better presence of the congress in the international forums; vi) employment of advanced research techniques and technology; vii) multi-and inter-disciplinary collaborations, and viii) no distinction among oral presentation and poster abstracts. Key Words: conference, sport sciences, scientific method